2017
DOI: 10.3390/f8110440
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Safety and Health Concerns in Logging: A Cross-Sectional Assessment in Virginia

Abstract: Abstract:Increased logging mechanization has helped improve logging safety and health, yet related safety risks and concerns are not well understood. A cross-sectional study was completed among Virginia loggers. Participants (n = 122) completed a self-administered questionnaire focusing on aspects of safety and health related to logging equipment. Respondents were at a high risk of workplace injuries, with reported career and 12-month injury prevalences of 51% and 14%, respectively. Further, nearly all (98%) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…5 Likewise, researchers in Virginia confirmed high rates of musculoskeletal disease symptoms (98%) in a separate study, but interestingly only work-related injury (not MSD symptoms) were positively related to years of experience. 6 Age was also not positively associated with back pain but rather with neck pain in logging workers in Southern United States. 5 Considering research that has focused on logging safety or health, much of it has taken place outside the Northeastern United States.…”
Section: Introductionmentioning
confidence: 81%
“…5 Likewise, researchers in Virginia confirmed high rates of musculoskeletal disease symptoms (98%) in a separate study, but interestingly only work-related injury (not MSD symptoms) were positively related to years of experience. 6 Age was also not positively associated with back pain but rather with neck pain in logging workers in Southern United States. 5 Considering research that has focused on logging safety or health, much of it has taken place outside the Northeastern United States.…”
Section: Introductionmentioning
confidence: 81%
“…Therefore, GNSS-based geofences should generally not be used to provide fine-resolution safety alerts to operators [ 13 ]. Real-time location sharing may still help improve general SA on the jobsite and has been identified as an important area for research and development in forest operations [ 13 , 20 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The body region most commonly reported as having symptoms included the lower back (49.2%) and knee (37.7%). 9 A cross-sectional study of French and Norwegian forest machine operators revealed organizational risk factors were related to adverse musculoskeletal health outcomes in the neck, shoulder, and wrist. 31 Other studies revealed Swedish LMOs also have high rates of neck pain and MSDs.…”
Section: Discussionmentioning
confidence: 99%
“…6,8 LMO work durations can be varied. Kim et al 9 reported 67.2% of surveyed LMOs in Virginia operated logging machinery more than eight or more hours per day. Mitchell et al 10 surveyed logging company owners who implemented shift work in seven Southeastern U.S. states and reported shift durations 7.5 and 12 hours per day.…”
Section: Introductionmentioning
confidence: 99%